PENGEMBANGAN KOMIK BERBASIS ETNOMATEMATIKA SEBAGAI MEDIA PEMBELAJARAN PADA MATERI BANGUN DATAR KELAS III SEKOLAH DASAR - Rona Anggraini; Muhammad Fendrik; Jesi Alexander Alim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a product in the form of an ethnomathematics-based comic as a learning medium for the material of flat shapes in grade III of elementary school which will be feasible and practical to be used in the learning process. The method used in this study is the development method or research & development (R & D). The model used in this development research is 4D which consists of four stages, namely Define, Design, Development, Dissimination. The subjects of the research trial were grade III students of SD Negeri 010 Talontam Benai. The instruments used were expert validation sheets, practicality questionnaires of student and teacher responses. The results of this study, the assessment of product feasibility by validators of material experts, media experts, and language experts with an overall average percentage of 91.85% with a very valid category. And the practicality test conducted by the teacher obtained an overall average percentage of 92.38% with a very practical category. And the one to one trial obtained an average of 93% with a very practical category, and the limited test conducted obtained an average of 92.18% with a very practical category. Thus, ethnomathematics-based comics are feasible and practical to use.